Antarctic activities of the Milano Bicocca Radio Group: a Status Report - BOELLA, GIULIANO FILIPPO; GERVASI, MASSIMO; PASSERINI, ANDREA; SIRONI, GIORGIO; ZANNONI, MARIO; Tartari, A (Istituto Nazionale di Astrofisica, 2003)
The Milano Bicocca Radio Group has a long experience of astrophysical and cosmological observations made at the Amundsen Scott Base at South Pole, Terra Nova Bay and at Dome C with existing equipment and ad hoc experiments. Present activities are in the field of CMB Polarimetry and Radiometry at mm and sub-mm wavelengths.